Proceedings of the Genetic and Evolutionary Computation Conference 2021
DOI: 10.1145/3449639.3459399
|View full text |Cite
|
Sign up to set email alerts
|

Explorative data analysis of time series based algorithm features of CMA-ES variants

Abstract: In this study, we analyze behaviours of the well-known CMA-ES by extracting the time-series features on its dynamic strategy parameters. An extensive experiment was conducted on twelve CMA-ES variants and 24 test problems taken from the BBOB (Black-Box Optimization Bench-marking) testbed, where we used two different cutoff times to stop those variants. We utilized the tsfresh package for extracting the features and performed the feature selection procedure using the Boruta algorithm, resulting in 32 features t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…We believe that the regression models can strongly benefit from this information; possibly not in the naïve way applied in [5] (where only the final state variables at the time of the switch were used as features for the regression model), but by extracting information from the evolution of the state variables during the first part of the optimization process, before the switch. Such an approach based on time-series analysis have been suggested in the literature [44]. There, it was shown that features computed on evolution of the state variables of the CMA-ES can be used to accurately classify variants of the algorithm, and predict which of the BBOB problems was being optimized.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the regression models can strongly benefit from this information; possibly not in the naïve way applied in [5] (where only the final state variables at the time of the switch were used as features for the regression model), but by extracting information from the evolution of the state variables during the first part of the optimization process, before the switch. Such an approach based on time-series analysis have been suggested in the literature [44]. There, it was shown that features computed on evolution of the state variables of the CMA-ES can be used to accurately classify variants of the algorithm, and predict which of the BBOB problems was being optimized.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the regression models can strongly benefit from this information; possibly not in the naïve way applied in [5] (where only the final state variables at the time of the switch were used as features for the regression model), but by extracting information from the evolution of the state variables during the first part of the optimization process, before the switch. Such an approach based on time-series analysis have been suggested in the literature [43]. There, it was shown that features computed on evolution of the state variables of the CMA-ES can be used to accurately classify variants of the algorithm, and predict which of the BBOB problems was being optimized.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies explored the family of modular CMA-ES in different learning settings including exploratory analysis of CMA-ES [9], automated algorithm performance prediction [31], automated algorithm selection [16], and automated algorithm configuration [5,29].…”
Section: Introductionmentioning
confidence: 99%
“…De Nobel et al [9] analyzed the CMA-ES behavior by using timeseries features extracted from its dynamic strategy parameters. Their results showed that these features can be used to classify isolated CMA-ES modules and have the potential to be used in the prediction of their performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation